Experimental study of the characteristics of various types of filling coils for intracranial aneurysm embolisation. Issue 5 (October 2018) - Ito, Masashi; Matsubara, Noriaki; Izumi, Takashi; Miyachi, Shigeru; Ota, Keisuke; Imai, Tasuku; Nishihori, Masahiro; Wakabayashi, Toshihiko
Background: In endovascular embolisation for an intracranial aneurysm, after framing coil deployment, soft coils (often called filling coils) are usually selected to fill inside the cage of previous coils. Various kinds of filling coils are available, although each coil has its own characteristics. Understanding their differences to ensure proper coil selection is important to achieve successful embolisation. The purpose of this study was to investigate the characteristics of various filling coils. Materials and methods: The authors developed a radiolucent coil to evaluate the performance of coils under conditions simulating the course of embolisation. Experimental embolisation was performed by using a silicone aneurysm filled with radiolucent coils. Indices including area, circularity, centroid position and coefficient of variation were investigated by analysing the figures of the filling coils after being inserted into the radiolucent coil under fluoroscopy. Results: The characteristics of each coil depended on the coil design. The helical coil had the highest circularity and centroid position scores and lowest area score. Therefore, it tended to develop a compacted mass. The low shape-memory coil had the lowest circularity, second-highest centroid position and highest coefficient of variation scores. Therefore, it tended to develop irregularly shaped distribution with low reproducibility. Complex coils generally had higher area and circularity scores. Therefore, they tended to provide a balanced distribution with relatively expanded mass and less small compartmentation. Conclusions: The evaluated characteristics of various filling coils should be useful for appropriate selection of filling coils.